2001
DOI: 10.1073/pnas.191313598
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of short- and long-term caloric restriction effects in the liver of aging mice

Abstract: We present genome-wide microarray expression analysis of 11,000 genes in an aging potentially mitotic tissue, the liver. This organ has a major impact on health and homeostasis during aging. The effects of life-and health-span-extending caloric restriction (CR) on gene expression among young and old mice and between long-term CR (LT-CR) and short-term CR (ST-CR) were examined. This experimental design allowed us to accurately distinguish the effects of aging from those of CR on gene expression. Aging was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
248
6
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(290 citation statements)
references
References 59 publications
35
248
6
1
Order By: Relevance
“…It is documented that human and experimental gliomas are dependent on glycolysis for energy (Mies et al, 1990;Ikezaki et al, 1992;Oudard et al, 1997), and that DR-induced caloric restriction reduces glycolytic energy and down-regulates glycolytic gene expression (Lee et al, 2000;Cao et al, 2001;Greene et al, 2001). Additionally, the DR-induced down regulation of glycolysis should also reduce the level of pyruvic acid, a glycolytic end product with angiogenic activity .…”
Section: Discussionmentioning
confidence: 99%
“…It is documented that human and experimental gliomas are dependent on glycolysis for energy (Mies et al, 1990;Ikezaki et al, 1992;Oudard et al, 1997), and that DR-induced caloric restriction reduces glycolytic energy and down-regulates glycolytic gene expression (Lee et al, 2000;Cao et al, 2001;Greene et al, 2001). Additionally, the DR-induced down regulation of glycolysis should also reduce the level of pyruvic acid, a glycolytic end product with angiogenic activity .…”
Section: Discussionmentioning
confidence: 99%
“…RNA differential displays and the serial assessment of gene expression (Welle et al, 2001) have been applied to explore senescence-associated genes to gain an insight into the molecular mechanisms underlying senescence. Moreover, recent advances in cDNA array technology have made it possible to analyze global gene expressions, and a variety of genes involved in cell cycle regulation, immune and inflammation, cytoskeleton, stress response, and metabolism are known to be altered during cellular senescence (Shelton et al, 1999;Ly et al, 2000;Zhang et al, 2003) and animal models (Lee et al, 1999(Lee et al, , 2000Tollet-Egnell et al, 2001;Kayo et al, 2001;Cao et al, 2001). Shelton et al (1999) assessed senescence-associated gene expression in dermal fibroblasts using a 1 k cDNA microarray and concluded that the senescent state mimics inflammatory wound repair processes.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to understanding the molecular mechanisms whereby diet alters health is to identify diet-regulated genes that cause or contribute to disease process. This can be done by examining the expression of a candidate gene or groups of genes (e.g., 142) in response to diets, an approach pioneered by Goodridge (17,94,95,121). DNA and oligo-array technologies have extended this approach to multiple genes within a pathway (36) or all genes on an array (17,94,162; reviewed in Refs.…”
Section: Some Diet-regulated Genes Can Play a Role In Chronic Diseasesmentioning
confidence: 99%
“…This can be done by examining the expression of a candidate gene or groups of genes (e.g., 142) in response to diets, an approach pioneered by Goodridge (17,94,95,121). DNA and oligo-array technologies have extended this approach to multiple genes within a pathway (36) or all genes on an array (17,94,162; reviewed in Refs. 66,141,145,155).…”
Section: Some Diet-regulated Genes Can Play a Role In Chronic Diseasesmentioning
confidence: 99%